Occupational and sociodemographic characteristics in relation to the perception of stress in military policemen Características ocupacionais e sociodemográficas relacionadas ao estresse percebido de policiais militares Características ocupacionales y sociodemográficas relacionada con la percepción del estrés en policías militares - de Liz C.M.* (2014)
© 2014, Editorial Ciencias Medicas. All rights reserved.Introduction: in Brazil, the police work is considered one of the most stressful lines of work, not only due to the nature of activities involving high risk, but also to the work overload and the internal relations of the corporation, whose organization is based on a rigid hierarchy and military discipline. There are factors related to the biological state of health that derive from the psychological state, the environmental pressures and the economical resources; such factors predispose police to stress. Objective: to compare the stress perception in military policemen according to the occupational and sociodemographic characteristics. Methods: eighty six male military policemen aged 35 (± 8.3) years as average, who worked in a battalion in Florianópolis/SC, Brazil, participated in the study. The "Questionário de caracterização", the "Questionário de Classificação Socioeconômica ABEP/2008", the "Questionário dos Estágios para Mudança de Comportamento para o Exercício Físico" and the "Escala de Estresse Percebido (EEP)" were used. Descriptive and inferential analysis was made with α of 0.05 (p< 0.05). Results: the highest levels of perceived stress were found for sedentary policemen, for the ones aged up to 35 years, the ones that had already experienced a traumatic event in their careers, those who work in operational area of police service and in those with poor sleeping quality. Conclusions: stress is related to psychological and physical health of the individuals and therefore, interventions targeting the control and/or prevention of stress in military policemen, mainly those classified as the most affected ones, must be implemented by the battalions.